Formulasi Dan Evaluasi Sediaan Obat Kumur (Mouthwash) Dari Ekstrak Etanol Tanaman Bundung (Actinoscirpus Grossus) Sebagai Antiseptik Mulut - Noval Noval; Melviani Melviani; Novia Novia; Dahlia Syahrina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2020)
Research of mouthwash formulation and evaluation of bundung plants extract (Actinoscirpus grossus) as an oral antiseptic also has been tested in Streptococcus mutants bacteria by variation in the concentration of extract 2%, 2,5%, 3% and 3,5%, which aims to determine the most ideal formula in physical quality and has the highest antibacterial activity based on an inhibition zone of Streptococcus mutants bacteria in mouthwash formula. The methods used include the step of extraction of Bundung plants, preparation of mouthwash with 4 formula F1 (2%), F2 (2,5%), F3 (3%) and F4 (3,5%) followed by an evaluation that includes organoleptic, pH test, viscosity test and the test of inhibition zone bacteria. The test of inhibition zone bacteria used MHA media with diffusion method. Stability performed on weeks 1, 2, 3, 4, 5, and 6. The result showed variation in the concentration of extract bundung plants in a mouthwash formula has and effect on the diameter of the inhibition zone. But did not have a significant effect on the physical stability properties of the mouthwash formula. Mouthwash formula which has the highest antibacterial activity based on inhibition zone of Streptococcus mutants that is 3,5% contained in formula IV.